2014
DOI: 10.3390/s140405785
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Camera Networks for 3D Image Based Modeling of Cultural Heritage Objects

Abstract: 3D modeling of cultural heritage objects like artifacts, statues and buildings is nowadays an important tool for virtual museums, preservation and restoration. In this paper, we introduce a method to automatically design a minimal imaging network for the 3D modeling of cultural heritage objects. This becomes important for reducing the image capture time and processing when documenting large and complex sites. Moreover, such a minimal camera network design is desirable for imaging non-digitally documented artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…One suggestion is to reduce the number of images during the image matching and bundle adjustment procedures. Alsadik et al [27] filtered the image network with the minimal camera principle and then applied improvements through a compromise between coverage and model accuracy [44]. Similarly, Snavey et al [20] constructed a skeletal graph to process a large number of unordered collections.…”
Section: Performance and Analysismentioning
confidence: 99%
“…One suggestion is to reduce the number of images during the image matching and bundle adjustment procedures. Alsadik et al [27] filtered the image network with the minimal camera principle and then applied improvements through a compromise between coverage and model accuracy [44]. Similarly, Snavey et al [20] constructed a skeletal graph to process a large number of unordered collections.…”
Section: Performance and Analysismentioning
confidence: 99%
“…4. In a research case study, the mean point error from a modern close range photogrammetric workflow was confirmed to be less than 5mm for signalized points and up to 1.5cm in poorly textured areas (Alsadik, 2014).…”
Section: D Documentation By Structure-from-motionmentioning
confidence: 99%
“…Usually, optimal image acquisition patterns and networks are a key issue in high-quality 3d reconstructions (Alsadik et al, 2014). However, in cases where tourist photographs provide the main source of imagery, acquisition patterns become a limiting factor.…”
Section: Image Acquisition Patternsmentioning
confidence: 99%
“…and Santagati et al (2013) specifically investigate the accuracy potential of image-based 3d reconstructions by comparing their results with terrestrial LiDAR reference data sets. Alsadik et al (2014) furthermore describe methods for automatically designing minimal networks for the 3d modelling of cultural heritage. These professional photogrammetric reconstructions with specifically designed networks stand in contrast to numerous research efforts exploiting the potential of unordered web-based image collections for efficiently reconstructing large-scale urban environments (e.g.…”
Section: Introductionmentioning
confidence: 99%